Proceedings of the 2nd International Conference on Research of Educational Administration and Management (ICREAM 2018) 2019
DOI: 10.2991/icream-18.2019.19
|View full text |Cite
|
Sign up to set email alerts
|

How Professional Learning Community Based Academic Supervision Model Improves Teachers’ Performance

Abstract: This paper outlines how academic supervision based on professional learning community improves teachers' performance. Performance issues affect teachers' academic quality and academic supervision is one way to resolve those issues. Thus, academic supervision is expected to improve teachers' quality. In its implementation, academic supervision should be based on Professional Learning Community (PLC). In PLC-based effort, the management of various school conditions is aimed towards building a dialogue between ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Based on the study results, it was shown that the principal's academic supervision had a significant impact on improving the performance and quality of learning at SMP Negeri 2 Kroya and had a significant effect on professional guidance assistance. As the highest leader, the principal is essentially a person who understands and masters effective managerial and supervision (Komariah et al, 2019;Lian et al, 2019). Successful supervision at SMP Negeri 2 Kroya is shown by the ability of the principal to carry out effective learning, form good leadership characteristics, develop staff, manage teaching staff, to be able to form a responsive and anticipatory attitude in school personnel, be able to bring the school towards change towards a better direction, good ability to create a safe and orderly school environment (Azwardi, 2020) .…”
Section: Results and Discussion Professional Guidance Assistancementioning
confidence: 99%
“…Based on the study results, it was shown that the principal's academic supervision had a significant impact on improving the performance and quality of learning at SMP Negeri 2 Kroya and had a significant effect on professional guidance assistance. As the highest leader, the principal is essentially a person who understands and masters effective managerial and supervision (Komariah et al, 2019;Lian et al, 2019). Successful supervision at SMP Negeri 2 Kroya is shown by the ability of the principal to carry out effective learning, form good leadership characteristics, develop staff, manage teaching staff, to be able to form a responsive and anticipatory attitude in school personnel, be able to bring the school towards change towards a better direction, good ability to create a safe and orderly school environment (Azwardi, 2020) .…”
Section: Results and Discussion Professional Guidance Assistancementioning
confidence: 99%
“…Improving the achievement of academic supervision results is supported by implementing academic supervision that utilizes technology in the academic supervision process (Sugiyono et al, 2019). The role of technology in the academic supervision process facilitates the assessment and evaluation of learning carried out by teachers and school supervisors (Komariah et al, 2019). Pahlevie research shows that the role of technology is a differentiator in the academic supervision process in-class visits.…”
Section: Levene's Test For Equality Of Variancesmentioning
confidence: 99%
“…Performance systems generally include behavior (what employees do) and results (results from employee behavior). The performance dimension does not include the results of the behavior, but the behavior itself [20], [35]. So performance is about behavior or what employees do, not what is produced or what results from their work.…”
Section: Teacher Performancementioning
confidence: 99%